Laboratory investigation on the compressibility of Singapore marine clays. Issue 6 (18th August 2017) - Bo, Myint Win; Choa, Victor; Chu, Jian; Arulrajah, Arul; Horpibulsuk, Suksun
ABSTRACT: The compressibility characteristics of Singapore marine clay in reconstituted and undisturbed states were studied using oedometer, constant rate of strain, Rowe cell, and isotropic consolidation tests. The intrinsic compression curve of the reconstituted clay was found to be similar to that proposed earlier with some minor deviations at low vertical stresses of less than 100 kPa. The field and laboratory compression behaviors were found to be similar, hence the laboratory curve could be used as a reference for interpreting the field behavior. Factors affecting the measurements of compression index and yield stress were discussed. As the coefficient of lateral earth pressure at the top upper clay was close to 1, the compression curves of vertically and horizontally trimmed samples were almost similar. The yield stress was mainly controlled by the strain rate; i.e., the higher strain rate resulted in the higher yield stress. Constrained modulus as derived from cone penetration tests and flat dilatometer tests were also examined and compared with laboratory test results. The in situ tests showed the decrease in constrained modulus with depth and generally the dilatometer test was found to register a higher modulus value.